The New Policy on Library in Indonesia Facing the Industrial Era 4.0: Opportunities and Challenges - Iwan Permadi; Gabriel Wahyu Purnomo; Kurniasih Yuni Pratiwi (Wacana Journal of Social and Humanity Studies, 2022)
Libraries in Indonesia certainly have directions and policies to keep pace with the progress and development of knowledge needs in this 4.0 industrial era. This study aims to analyze the opportunities and challenges of libraries in Indonesia in determining new directions and policies facing the industrial era 4.0. This study uses a type of qualitative method with a descriptive approach. Data analysis was carried out using the interactive model of (1), which included data condensation, data presentation, and conclusion. The results of this study found that there are several directions and policies implemented and prepared by libraries in Indonesia facing the industrial era 4.0, namely directions and policies that focus on the management of collection by 10% by increasing the number of digital collections and developing library services towards digital libraries; directions and policies that focus on the management of knowledge by 20%, by optimizing library automation systems; and directions and policies that focus on the transfer of knowledge by 70%, by increasing the availability of working space, class library programs, as well as various training programs and user assistance. Keywords: new library policies, management of collection, management of knowledge, transfer of knowledge, industrial era 4.0